Analyzing the Impact of IRS Actions on Tax Compliance from Individuals to Corporate Entities - Kurnia, Mega (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This study aims to investigate the multifaceted dynamics of tax compliance behavior in individuals and corporate entities and explain the impact of IRS actions on compliance outcomes. Research Design and Methodology: The study's methodology involved a comprehensive analysis of existing literature and empirical evidence, synthesizing findings from multiple disciplinary perspectives. Findings and Discussion: The study found that enforcement measures, such as audits and sanctions, significantly influence deterring non-compliance and encouraging voluntary compliance with tax laws. This research also highlights the role of psychological motivation, organizational norms, and community perceptions in compliance decision-making. Implications: The study emphasizes the importance of a balanced and nuanced approach to enforcement strategies and the need for further studies to explore the complex interactions between taxpayer education, enforcement actions, and compliance behavior.